Income Smoothing as Rational Equilibrium Behavior. - Lambert, Richard A. (The Accounting Review, 1984)
ABSTRACT: This paper uses agency theory to examine the phenomenon of "real" income smoothing. The analysis suggests that incentive problems caused by the unobservability of a manager's actions can lead to the manager selecting actions at the end of a period to smooth the period's income toward its ex ante expected value. An important feature of the analysis is that both the principal and the manager are modeled as rational parties. In particular, the principal can predict what actions the manager will choose in response to any compensation scheme, and he takes this into consideration in deciding what compensation plan to offer. The analysis shows that the optimal compensation scheme offered by the principal causes the manager to smooth the firm's income. Income smoothing can therefore arise as optimal equilibrium behavior.